Visualization analysis of prevention of deep venous thrombosis of lower limbs based on CiteSpace - DENG Xin, SU Yun, WU Di, FU Yutian, ZHANG Haochun, ZHANG Yongkun (Zhongguo linchuang yanjiu)
Objective：This study conducts a visual analysis to explore the research focus on deep vein thrombosis (DVT) prevention in China. Methods：Literature related to DVT prevention published on China National Knowledge Infrastructure (CNKI) from 2012 to 2024 were searched. The data of authors, research institutions, and keywords were visual analysed using CiteSpace 6.3.R3 software. Results： A total of 2 056 eligible studies were included in the analysis. The publication volume showed an increasing trend from 2014 to 2018 but started declining from 2019. Visual maps revealed 260 contributing authors, with 4 authors publishing at least 3 articles. Notable authors included LI Na, FU Yahui, LI Juan and ZHANG Yanzhao. The research involved 189 institutions, with 34 institutions publishing three or more articles. Fujian University of Traditional Chinese Medicine and Guangzhou University of Traditional Chinese Medicine each contributed over 15 articles. A total of 262 keywords were identified, with 69 keywords appearing ten or more times, including “nursing”, “nursing interventions”, “lower limb fractures”, and “cesarean section”.Conclusion：Research interest in DVT prevention has shown a declining trend in recent years but remains significant. Collaboration between research institutions is limited, and studies primarily focus on clinical aspects with varying evaluation standards. Basic research is still insufficient. Enhancing collaboration, standardizing evaluation criteria, and strengthening foundational research can provide comprehensive and effective measures for clinical DVT prevention in future studies.